SISTEM REKRUTMEN, SELEKSI DAN PENGGAJIAN GURU UNTUK PENINGKATAN KINERJA GURU DI SMK KESEHATAN FAHD ISLAMIC SCHOOL - Febryan Hadinata (UNISAN JURNAL, 2023)
The purpose of this research is to answer the formulation of the problem, namely to find out the recruitment, selection and payroll systems and the influence of these three systems on teacher performance. This research is a qualitative research with the aim of describing the situation in the field regarding the system of recruitment, selection and remuneration on teacher performance. Data were obtained through in-depth interviews, observations, document studies and documentation which were carried out on April 14 and 18 April 2022. Data analysis by means of data reduction, presenting research and drawing conclusions. The results of research at the Fahd Islamic School Health Vocational School, namely: (1) The recruitment system has been running well by using internal sources in the form of recommendations from teachers who have taught and external sources by posting on social media. (2) The selection system starts from the selection of application files, the first calling of candidates for interviews and candidates who pass the interview will take part in the final stage, namely microteaching and medical tests. The work statement contains points that must be obeyed by the accepted teacher candidate. Constraints in the recruitment and selection system exist at 'time' where it is difficult to adjust schedules with candidates. However, with active communication this obstacle can be overcome. (3) The salary calculation system follows the provisions of the foundation and is paid on the 15th of each month. In addition to the teacher's salary, they get transportation money, food money, activity money and THR. There are no problems in payroll because it is computerized. (4) Appropriate recruitment and selection produces teachers with quality performance while proper remuneration increases teacher performance to be more serious and love the profession.